2012
DOI: 10.1002/jbm.a.34519
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐layer supramolecular assemblies based on linear and star‐shaped poly(glycerol methacrylate)s for doxorubicin delivery

Abstract: Hollow microcapsules, composed of pH responsive polyelectrolytes via a layer-by-layer (LBL) adsorption technique, were prepared. Linear or star-shaped poly(glycerol metha crylate)s (PGOHMAs) modified with 1,4-butanediamine and 1,2-ethanediamine (EDA) were synthesized and used as polycations. Poly(acrylic acid) was employed as polyanion and SiO2 (about 170 nm) as template. After LBL absorption, SiO2 cores were removed by HF treatment. The particle size and zeta potential were measured by dynamic light scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Wang et al coated the mesoporous silica spheres with oppositely charged PE (poly(acrylic acid) (PAA) and poly(allylamine hydrochloride) using this method. Sun et al prepared a star‐shaped 1,2‐ethanediamine modified poly(glycerol methacrylate)s hollow microcapsule using the similar procedure, which presented high loading capacity and entrapment efficiency for doxorubicin hydrochloride. The “graft to” method is to establish a chemical bond between the chain end of the polymer molecules and the surface of MSN.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al coated the mesoporous silica spheres with oppositely charged PE (poly(acrylic acid) (PAA) and poly(allylamine hydrochloride) using this method. Sun et al prepared a star‐shaped 1,2‐ethanediamine modified poly(glycerol methacrylate)s hollow microcapsule using the similar procedure, which presented high loading capacity and entrapment efficiency for doxorubicin hydrochloride. The “graft to” method is to establish a chemical bond between the chain end of the polymer molecules and the surface of MSN.…”
Section: Introductionmentioning
confidence: 99%
“… 47 51 Previously, we have shown that nanocapsules fabricated from star-shaped bis-aminated PGOHMA (BA-PGOHMA) and poly(acrylic acid) (PAA) using the layer-by-layer (LbL) self-assembly method are pH-responsive and undergo targeted release of their cargo, indicating they are promising candidates as gate components on MSNs for drug delivery and gene therapy. 52 55 In the conventional polymeric nanocarrier systems, the cargo are usually linked covalently or attached noncovalently to the supporting materials by weak van der Waals interactions, and are released upon application of appropriate stimuli. 11 On the other hand, supramolecular polymers have been utilized for controlled cargo release because of their unique abilities as superamphiphilic polymers 56 and LbL materials.…”
mentioning
confidence: 99%
“… 11 On the other hand, supramolecular polymers have been utilized for controlled cargo release because of their unique abilities as superamphiphilic polymers 56 and LbL materials. 52 , 57 66 To the best of our knowledge, however, stimuli-responsive LbL supramolecular polymers have not been employed as gating materials on MSN surfaces for controlled drug delivery. In this paper, we demonstrate that cucurbit[7]uril 67 76 (CB[7]) can serve as a kind of supramolecular glue 77 between layers of BA-PGOHMA polymers, i.e., EDA-PGOHMA, BDA-PGOHMA, and HDA-PGOHMA derived from 5-arm poly(glycidyl methacrylate) (PGMA) with ethanediamine (EDA), 1,4-butanediamine (BDA), and 1,6-hexamethylenediamine (HDA), respectively, via ion–dipole interactions to form stable supramolecular polymers on the surface of cargo-loaded MSNs (Figure 1 ).…”
mentioning
confidence: 99%
“…Polyelectrolyte capsules of PGMAs responsive to pH were successfully constructed by us using LbL assembly. 117 LbL assembly of multilayer films onto the surfaces of colloidal particles followed by template removal is a facile and versatile method to construct functional capsules at the nanometer-level with controlled size, shape, composition, and wall thickness. Monodisperse poly(acrylic acid), i.e., PAA, is rich in COO À groups and is employed as polyanions.…”
Section: Polymeric Capsulesmentioning
confidence: 99%